A Quantitative Assessment of the Finance–Growth–Innovation Nexus in EEA Countries: Evidence from a Multivariate VECM. Issue 3 (3rd July 2019) - Pradhan, Rudra P.; Hall, John H.; Gupta, Atul; Nishigaki, Yasuyuki; Filho, Flávio de São Pedro; Toit, Elda du
Abstract: This paper uses country-level data of European Economic Area countries between 1989 and 2016 to examine the interactions between economic growth, innovation, and financial market activities, with specific reference to the bond and insurance markets. Our intent is to know whether causality runs among these variables both ways, or not at all. Using a vector error correction model, the study finds that financial market activities and economic growth determine innovation activities in these countries. Additionally, the study also finds bidirectional Granger causality between financial market activities and economic growth, as well as between innovation activities and economic growth.